Analysis of influence of internal Coulomb friction on the deformation of composite materials. - Багрій, О.В. (Problems of Tribology, 2015)
In work investigated dependence of the values of the shear modulus and Poisson’s ratio of the achieved level of the stress-strain state. This makes it possible to use the value obtained in solving planar physically nonlinear problems of the mechanics of discrete materials on numerical methods